SOSIALISASI MAHASISWA INDO GLOBAL MANDIRI PENGEMBANGAN COFFEE SHOP KOPI EKSIS PKM MENGGUNAKAN E-COMMERCE - Argeto , Valentino; Karina, Arihta; Hertati, Lesi; Terttiaavini; Heryati, Agustina; Asmawati (Transpublika Publisher, 2021)
This research aims to expand the existing coffee sales network from offline channels to include e-commerce platforms, specifically utilizing social media accounts. In the modern era of rapidly developing technology, new innovations have captivated the interest of young people. Coffee shops have evolved to offer modern facilities, a diverse food menu, e-money payment options, and fast, free internet access, all of which attract young customers. Eksis Coffee is situated in Palembang, at the heart of the city's trendy and modern red-eye area, although it remains relatively unknown due to its location on the outskirts. Young people perceive coffee shops as prestigious, offering practicality and convenience compared to simpler alternatives. This adoption of a new lifestyle serves to establish one's identity in the surrounding environment, particularly among young individuals who heavily rely on social media.